SPE Gas Technology Symposium 1998
DOI: 10.2118/39972-ms
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Linear Flow in Gas Well Production

Abstract: This paper was selected for presentation by an SPE Program Commdtee following rwew of information contahed in anqbstract submitted by the author(s). Contents cd the paper, as -fed. * n~~0 M* by Me .%cw@ d Petroleum Engineam and are subject to corr~on by the atithor(s) lle material, as presantad, does not necessarily reflect any position of the Sochty C4Ps4roleum Enginaars, its officers, or members Papers presented ad SPE meetings are subject to publication review by Editorial Commtiees of the Society of Petrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…Therefore, the equations presented here are based on the assumption of a constant flowing pressure at the well. Linear-flow theory El-Banbi and Wattenbarger 1998) indicates that at a constant flowing pressure, a plot of inverse gas rate vs.…”
Section: Basic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the equations presented here are based on the assumption of a constant flowing pressure at the well. Linear-flow theory El-Banbi and Wattenbarger 1998) indicates that at a constant flowing pressure, a plot of inverse gas rate vs.…”
Section: Basic Modelmentioning
confidence: 99%
“…7 into Eq. 6, the following equation is obtained for calculating the duration of linear flow and, hence, the beginning of boundary-dominated flow El-Banbi and Wattenbarger 1998):…”
Section: Basic Modelmentioning
confidence: 99%
“…The most popular method for analyzing linear flow is the square-root-of-time plot, a plot of rate-normalized pressure versus square root of time. It is documented in the literature that linear flow appears as a straight line on the square-root-of-time plot El-Banbi and Wattenbarger, 1998). Nobakht and Clarkson (2011a) showed that this is not true for constant rate gas production.…”
Section: Introductionmentioning
confidence: 99%
“…Linear flow theory El-Banbi and Wattenbarger, 1998) indicates that at a constant flowing pressure, a plot of inverse gas rate versus square root of time on Cartesian coordinates is a straight line. The slope of this line is used in the literature to calculate x f ffiffi ffi k p…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation